2010
DOI: 10.1016/j.jenvman.2010.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Application of sludge-based carbonaceous materials in a hybrid water treatment process based on adsorption and catalytic wet air oxidation

Abstract: This paper describes a preliminary evaluation of the performance of carbonaceous materials prepared from sewage sludges (SBCMs) in a hybrid water treatment process based on adsorption and catalytic wet air oxidation; phenol was used as the model pollutant. Three different sewage sludges were treated by either carbonisation or steam activation, and the physico-chemical properties of the resultant carbonaceous materials (e.g. hardness, BET surface area, ash and elemental content, surface chemistry) were evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 20 publications
(23 reference statements)
1
13
0
Order By: Relevance
“…He reported S BET and micropore volume of 265 m 2 /g and 0.11 cm 3 /g when the sludge was activated at 838 °C and 80 min contact time. Other related studies conducted under similar activation conditions reported comparable values of obtained surface areas [ 42 , 53 , 54 ]. Compared to steam activation, CO 2 proved promising in producing better textural properties of SBAC.…”
Section: Sbac Production Processessupporting
confidence: 63%
See 2 more Smart Citations
“…He reported S BET and micropore volume of 265 m 2 /g and 0.11 cm 3 /g when the sludge was activated at 838 °C and 80 min contact time. Other related studies conducted under similar activation conditions reported comparable values of obtained surface areas [ 42 , 53 , 54 ]. Compared to steam activation, CO 2 proved promising in producing better textural properties of SBAC.…”
Section: Sbac Production Processessupporting
confidence: 63%
“…However, the low S BET and dominant mesoporous structure was attributed to high ash content of sludge that limits the development of microporous structures. In another study, Julcour Lebigue et al [ 42 ] carried out carbonization of two sludges with ash contents of 20% and 40% at 900 °C among which which the latter yielded the highest S BET of 180 m 2 /g. Numerous studies have also corroborated similar behaviors [ 43 , 44 ].…”
Section: Sbac Production Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…The AD-OX process was first described and assessed for phenol/4-hydroxybenzoic acid mixture in a large reactor used for preliminary scale up 20 . In order to reduce the adsorption time for many successive runs, a small automated reactor was built up and tested with various effluents and activated carbons: examples are reported by Krou 22 for phenol and tartrazine solutions, as well as real effluent issued from biological treatment of industrial wastewater up to 20 cycles, and Julcour Lebigue et al 21 using commercial AC and carbonaceous materials issued from sewage sludge. Similar general trends were observed with all these systems.…”
Section: Introductionmentioning
confidence: 99%
“…25 In this perspective, different alternative adsorbents are desirable to overcome these kinds of problems. [26][27][28] In this context, natural clays appear as interest natural adsorbents to clean polluted air, since their application could result in a cost-effective process for VOCs removal. Natural clays are quite abundant and their low costs are likely to become strong adsorbent candidates for the removal of VOCs from air.…”
mentioning
confidence: 99%